AB0870 Multiplexed Verification of Osteoarthritis Biomarker Protein Candidates in Human Serum Samples. (9th June 2015) - Fernandez Puente, P.; Fernandez-Costa, C.; Calamia, V.; Mateos, J.; Rocha, B.; Lourido, L.; Ruiz-Romero, C.; Blanco, F.J.
Abstract : Background: The diagnosis methods currently available for Osteoarthritis (OA) are limited and lack sensitivity. There is a considerable interest pointed in the validation of specific OA biomarkers for early diagnosis and disease progression studies in OA. Recently, there has been a remarkable development in mass spectrometry-based methodologies for the verification and validation of biomarkers with high specificity and sensitivity, since the multiple reaction monitoring (MRM) assay can measure several targets (peptides) with high sensitivity and throughput in biological samples. Objectives: The aim of this work was to verify a panel of OA biomarker candidates using the MRM technology. Methods: 100 serum samples were obtained from OA patients at different stages of the disease (K/L grade II, K/L grade IV and control donors). Serum proteins were quantified and digested with trypsin. The peptide mixture was separated by nano-LC coupled to a 5500 QTRAP mass spectrometer. A single multiplexed MRM assay was used to quantitate the levels of seven proteins (identified as putative OA biomarker candidates in shotgun proteomic experiments performed previously by our group) at different stages of OA, and compared to control donors: Pigment epithelium derived factor, Haptoglobin, Von Willebrand factor, Fructose-bisphosphate aldolase A, Insulin-like growth factor-binding protein complex acid labile subunit, C-type lectin domain family 3 member A and matrix metallopeptidase 2. Four MRM transitions per peptide were monitored and at least 2 peptides by protein were chosen. Stable synthetic isotope-labeled peptides were used as an internal standard control for each peptide. The relative quantification values of peptides were determined by calculating the ratio of peak areas from transitions of target peptides in OA and control samples, normalized to the peak area of the internal standard. Data analysis was performed using the Skyline software. Results: Haptoglobin and Von Willebrand factor were found quantitatively altered in the serum of OA patients compared to control donors using the MRM technology. As shown in Table I, these two proteins were found to be increased in OA serum samples compared to control donors, with a significant p-value and using two proteotypic peptides and several transitions for each peptide. Conclusions: A multiplexed method for the simultaneous quantification of a panel of seven proteins in serum has been developed, which is based on liquid chromatography-multiple reaction monitoring (LC-MRM) mass spectrometry. By these means, two novel putative OA serum protein biomarkers, Von Willebrand factor and Haptoglobin, were verified in a large cohort of individual serum samples. Further qualification studies will be necessary to establish their usefulness for OA diagnosis and progression studies. Disclosure of Interest: None declared